Shared Decision Making in Primary Care Based Depression Treatment: Communication and Decision-Making Preferences Among an Underserved Patient Population - Matthews, Elizabeth B.; Savoy, Margot; Paranjape, Anuradha; Washington, Diana; Hackney, Treanna; Galis, Danielle; Zisman-Ilani, Yaara (Frontiers in Psychiatry, 2021)
Objectives: Although depression is a significant public health issue, many individuals experiencing depressive symptoms are not effectively linked to treatment by their primary care provider, with underserved populations have disproportionately lower rates of engagement in depression care. Shared decision making (SDM) is an evidence-based health communication framework that can improve collaboration and optimize treatment for patients, but there is much unknown about how to translate SDM into primary care depression treatment among underserved communities. This study seeks to explore patients’ experiences of SDM, and articulate communication and decision-making preferences among an underserved patient population receiving depression treatment in an urban, safety net primary care clinic. Methods: Twenty-seven patients with a depressive disorder completed a brief, quantitative survey and an in-depth semi-structured interview. Surveys measured patient demographics and their subjective experience of SDM. Qualitative interview probed for patients’’ communication preferences, including ideal decision-making processes around depression care. Interviews were transcribed verbatim and analyzed using thematic analysis. Univariate statistics report quantitative findings. Results: Overall qualitative and quantitative findings indicate high levels of SDM. Stigma related to depression negatively affected patients’ initial attitude towards seeking treatment, and underscored the importance of patient-provider rapport. In terms of communication and decision-making preferences, patients preferred collaboration with doctors during the information sharing process, but desired control over the final, decisional outcome. Trust between patients and providers emerged as a critical precondition to effective SDM. Respondents highlighted several provider behaviors that helped facilitated such an optimal environment for SDM to occur. Conclusion: Underserved patients with depression preferred taking an active role in their depression care, but looked for providers as partner in this process. Due to the stigma of depression, effective SDM first requires primary care providers to ensure that they have created a safe and trusting environment where patients are able to discuss their depression openly.